Silicon dioxide composite ceramic doped with aluminum silicate salt as well as preparation method and application of silicon dioxide composite ceramic
Through the silica composite ceramic doped with aluminum silicate salt, the problem of too small pore size of the composite ceramic porous framework is solved through the improved preparation method, and the complete penetration of the resin and the improvement of material performance is achieved.
Patent Information
- Application Number
- CN202411809267.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The pore size of the existing composite ceramic porous skeleton is too small, making it difficult to achieve complete penetration of the resin, resulting in poor bending strength and transparency of the material.
By doped with aluminum silicate salt, the preparation method includes mixing aluminum compounds, silica, metal salts, binders and solvents, drying, dispersing, granulating, pressing, sintering, modification and resin penetration, to obtain composite ceramics with a skeleton pore diameter between 100 and 600 nm and a high porosity.
Complete penetration of resin is achieved, forming an interlocking structure between resin and skeleton, improving mechanical properties such as crack propagation ability, flexural strength and elastic modulus, and having higher material transparency.
Smart Images

Figure CN119638488A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dental materials, and in particular relates to a silicon dioxide composite ceramic doped with aluminum silicate, and a preparation method and application thereof. Background Art
[0002] Sodium aluminum silicate is a white amorphous fine powder, odorless and tasteless. In recent years, the use of sodium aluminum silicate powder to prepare composite ceramic porous skeletons has become a research hotspot in dental materials.
[0003] The pore size of existing composite ceramic porous frameworks is very small, which is not conducive to the penetration of resin and it is difficult to obtain fully infiltrated composite ceramics. This is because the sodium aluminum silicate powder used to prepare the composite ceramic porous framework has a small particle size and is composed of nanoparticles. The commercially available sodium aluminum silicate powder is a nanopowder or a micron powder obtained by a granulation method of a nanopowder, but this micron powder is actually a collection of nanopowders, and the obtained porous framework is still composed of nanoparticles, which cannot fundamentally change its green body sintering performance and framework pore size.
[0004] Chinese patent CN115894001 A discloses a high-hardness and wear-resistant composite ceramic composite material, which uses silicate glass powder containing potassium sodium aluminum silicate as raw material, and after compression molding, the blank is subjected to ultra-high cold isostatic pressing treatment, the blank is sintered at high temperature, immersed in a resin solution for full penetration after cooling, and isostatically solidified after warm isostatic pressing, and a high-hardness and wear-resistant composite ceramic composite material is obtained after cooling. However, the pore size of this skeleton blank is still very small, even smaller than that of a common skeleton, which is more unfavorable for the penetration of the resin, and a fully infiltrated composite ceramic cannot be obtained. Many tiny pores in the obtained material cannot be eliminated, which can be confirmed by the fact that most of its bending strength tests are below 170MPa. Summary of the invention
[0005] The purpose of the present invention is to provide a silica composite ceramic doped with aluminum silicate, and a preparation method and application thereof. The silica composite ceramic doped with aluminum silicate provided by the present invention has a large skeleton pore size and high porosity, which is conducive to complete penetration of resin.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a silicon dioxide composite ceramic doped with aluminum silicate, comprising a skeleton and a resin forming an interlaced interlocking structure with the skeleton;
[0008] The mass content of the skeleton is 70-90%, and the mass content of the resin is 10-30%;
[0009] The general formula of the skeleton is mX a O b pAl 2 O 3qSiO 2 , where m, p and q are the molar numbers of the oxide, 0.01≤m≤1, 0.05≤p≤1, q≥2, a ranges from 1 to 2, and b ranges from 1 to 3;
[0010] The X in the skeleton a O b It is a mixture of sodium oxide and other metal oxides or sodium oxide; the other metal oxides include one or more of potassium oxide, lithium oxide, alkaline earth metal oxide and transition metal oxide; the total molar number of the other metal oxides is less than the molar number of sodium oxide;
[0011] The pore size of the skeleton is 100-600 nm, and the porosity is 20-40%.
[0012] The present invention also provides a method for preparing the aluminum silicate-doped silicon dioxide composite ceramic described in the above scheme, comprising the following steps:
[0013] (1) mixing an aluminum compound, silicon dioxide, a metal salt, a binder and a solvent to obtain a slurry; the metal salt is a carbonate; the carbonate includes one or more of sodium carbonate, potassium carbonate, lithium carbonate, alkaline earth metal carbonate and transition metal carbonate;
[0014] (2) drying, dispersing and granulating the slurry in sequence to obtain a powder;
[0015] (3) pressing and sintering the powder in sequence to obtain a skeleton;
[0016] (4) The skeleton is modified, resin-infiltrated and cured in sequence to obtain a silica composite ceramic doped with aluminum silicate; the modification comprises: mixing the skeleton, silane coupling agent and modifying liquid, and then vacuum-infiltrating and impregnating them in sequence; the modifying liquid comprises ethanol and water.
[0017] Preferably, the sintering reaction is carried out in an air atmosphere; the sintering reaction includes a first heating stage, a first heat preservation stage, a second heating stage, a second heat preservation stage and a cooling stage which are carried out in sequence.
[0018] Preferably, the heating rate of the first heating stage is 2-7°C / min, and the heating time is 60-180min; the temperature of the first insulation stage is 400-500°C, and the insulation time is 120-300min; the heating rate of the second heating stage is 2.5-5°C / min, and the heating time is 120-240min; the temperature of the second insulation stage is 700-1000°C, and the insulation time is 120-480min; the cooling stage includes furnace cooling and air cooling in sequence; the final temperature of the furnace cooling is below 200°C; the final temperature of the air cooling is room temperature.
[0019] Preferably, the mixing is ball milling mixing; the rotation speed of the ball milling mixing is 20 to 60 rpm, and the time is 60 to 240 min.
[0020] Preferably, the drying is oven drying; the oven drying is vacuum oven drying or normal pressure oven drying; the temperature of the vacuum oven drying is 40 to 80°C and the pressure is -0.10 to -0.05 MPa; the temperature of the normal pressure oven drying is 50 to 100°C;
[0021] Preferably, the dispersion is grinding dispersion; the rotation speed of the grinding dispersion is 10 to 30 rpm, and the time is 10 to 60 min.
[0022] Preferably, the granulation is vibrating screen granulation or spray drying granulation; the target particle size of the granulation is 30 to 150 μm.
[0023] Preferably, the pressing comprises sequentially performing dry pressing and cold isostatic pressing; the dry pressing pressure is 4 to 10 MPa, and the holding time is 0.5 to 2 min.
[0024] Preferably, the cold isostatic pressing pressure is 100-300 MPa, and the holding time is 0.5-2 min.
[0025] Preferably, the resin infiltration comprises the following steps: mixing the modified skeleton with the resin liquid and sequentially performing vacuum semi-infiltration, vacuum full-infiltration and vacuum plastic sealing; the pressure of the vacuum full-infiltration is 0.1-1 Pa, and the infiltration time is 24-240 hours.
[0026] The present invention also provides the use of the aluminum silicate-doped silica composite ceramic described in the above scheme or the aluminum silicate-doped silica composite ceramic obtained by the preparation method described in the above scheme in the field of dentistry.
[0027] The present invention provides a silicon dioxide composite ceramic doped with aluminum silicate. The skeleton pore size of the silicon dioxide composite ceramic provided by the present invention is relatively large, the pore size is between 100 and 600 nm, the pore size is increased by about 3 to 20 times, the porosity is high, and it is easy for the resin liquid to fully penetrate the skeleton to form an interlocking structure of the resin and the skeleton. According to the Griffith microcrack extension theory, its crack extension resistance is stronger, and the macroscopic performance is that its mechanical properties such as flexural strength and elastic modulus are more excellent. At the same time, since the refractive index of aluminum silicate (sodium aluminum silicate, potassium aluminum silicate, etc.) is similar to that of silicon dioxide, which is basically between 1.46 and 1.47, the sintered skeleton is solidified after modification and full resin penetration, and the obtained composite ceramic porcelain block is uniform and has high transparency.
[0028] The present invention also provides a method for preparing the silicon dioxide composite ceramic doped with aluminum silicate described in the above scheme. In the preparation process of the present invention, a micron-level aluminum silicate component is obtained. Compared with the skeleton directly prepared with nano-level sodium aluminum silicate powder, the skeleton pore size of the nano-level sodium aluminum silicate powder sintered is 30.6nm, and the resin liquid is difficult to fully penetrate, resulting in an incomplete organic network formed, which ultimately affects the mechanical properties of the material. The micron-level sodium aluminum silicate powder will not be easily delaminated and cracked like nano-sodium aluminum silicate when dry-pressed. The prepared silicon dioxide skeleton has a relatively large pore size, which is between 100 and 600nm, and the pore size is increased by about 3 to 20 times. The porosity is high, which is easy for the resin liquid to fully penetrate the skeleton, forming an interlocking structure of the resin and the skeleton; and the sodium aluminum silicate is equivalent to a binder, which improves the connection strength of the silicon dioxide skeleton, and finally improves the hardness of the porous skeleton of the composite ceramic, which is significantly higher than the hardness of the simple silicon dioxide composite ceramic.
[0029] The present invention also provides the application of the aluminum silicate-doped silica composite ceramics described in the above scheme or the aluminum silicate-doped silica composite ceramics obtained by the preparation method described in the above scheme in the field of dentistry. The key indicators of the skeleton of the material suitable for dentistry are porosity and average pore size. The skeleton pore size of the silica composite ceramic provided by the present invention is relatively large, the pore size is between 100 and 600 nm, the porosity is high, and it is suitable for use in the field of dentistry and can be used to prepare a series of dental-related products. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 The present invention provides a scanning electron microscope energy spectrum analysis of the skeleton of the silicon dioxide composite ceramic doped with aluminum silicate. DETAILED DESCRIPTION
[0032] The present invention provides a silicon dioxide composite ceramic doped with aluminum silicate, comprising a skeleton and a resin forming an interlaced interlocking structure with the skeleton;
[0033] The mass content of the skeleton is 70-90%, and the mass content of the resin is 10-30%;
[0034] The general formula of the skeleton is mX a O b pAl 2 O 3 qSiO 2 , where m, p and q are the molar numbers of the oxide, 0.01≤m≤1, 0.05≤p≤1, q≥2, a ranges from 1 to 2, and b ranges from 1 to 3;
[0035] The X in the skeleton a O b It is a mixture of sodium oxide and other metal oxides or sodium oxide; the other metal oxides include one or more of potassium oxide, lithium oxide, alkaline earth metal oxide and transition metal oxide; the total molar number of the other metal oxides is less than the molar number of sodium oxide;
[0036] The pore size of the skeleton is 100-600 nm, and the porosity is 20-40%.
[0037] In the present invention, the skeleton of the aluminum silicate-doped silicon dioxide composite ceramic is preferably in the shape of a cuboid, and the size is preferably 18 mm×15 mm×13 mm.
[0038] The skeleton of the aluminum silicate-doped silicon dioxide composite ceramic provided by the present invention (sintered at 850° C.) was analyzed by scanning electron microscope energy spectrum. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that after removing the peaks of conductive carbon and gold, the atomic Na:Al:Si:O ratio is close to 1:1:2:6, which is similar to that of sodium aluminum silicate AlNaO 6 Si 2 The match indicates that sodium aluminum silicate is produced during sintering and aluminum silicate salt is obtained.
[0039] The present invention also provides a method for preparing the aluminum silicate-doped silicon dioxide composite ceramic described in the above scheme, comprising the following steps:
[0040] (1) mixing an aluminum compound, silicon dioxide, a metal salt, a binder and a solvent to obtain a slurry; the metal salt is a carbonate; the carbonate includes one or more of sodium carbonate, potassium carbonate, lithium carbonate, alkaline earth metal carbonate and transition metal carbonate;
[0041] (2) drying, dispersing and granulating the slurry in sequence to obtain a powder;
[0042] (3) pressing and sintering the powder in sequence to obtain a skeleton;
[0043] (4) The skeleton is modified, resin-infiltrated and cured in sequence to obtain a silicon dioxide composite ceramic doped with aluminum silicate.
[0044] The present invention mixes aluminum compounds, silicon dioxide, metal salts, binders and solvents to obtain slurry. In the present invention, the metal salt is preferably a carbonate, and the carbonate includes one or more of sodium carbonate, potassium carbonate, lithium carbonate, alkaline earth metal carbonate and transition metal carbonate; the alkaline earth metal carbonate preferably includes one or more of strontium carbonate, calcium carbonate, barium carbonate and magnesium carbonate; the transition metal carbonate is preferably zinc carbonate. The present invention greatly reduces the sintering reaction temperature of silicon dioxide by adding metal salts, achieving a good energy-saving effect; at the same time, the metal salt is also a high-temperature pore-forming agent, which works together with the binder to prevent the formation of closed pores due to sintering at too high a temperature.
[0045] In the present invention, the aluminum compound preferably includes one or more of aluminum silicate, aluminum oxide and aluminum hydroxide.
[0046] In the present invention, the molar ratio of the metal salt to the aluminum compound is preferably 0.01-1:0.01-1, and the molar number of the aluminum compound is not greater than the molar number of the metal salt, more preferably 0.1-0.8:0.1-0.8, and the molar number of the aluminum compound is not greater than the molar number of the metal salt, further preferably 0.3-0.5:0.3-0.5, and the molar number of the aluminum compound is not greater than the molar number of the metal salt.
[0047] In the present invention, the molar ratio of the aluminum compound to silicon dioxide is preferably 0.01-1:2.01-10, more preferably 0.1-0.7:3-8, and further preferably 0.3-0.5:5-7.
[0048] In the present invention, the binder preferably includes one or more of polyvinyl alcohol, fatty alcohol polyoxyethylene ether, polyacrylamide, polyacrylic acid salt and sodium lignin sulfonate; the polyvinyl alcohol is preferably 1778 type polyvinyl alcohol; the binder is preferably used in the form of an aqueous solution, and the concentration of the aqueous solution is preferably 2-5wt%, more preferably 3-4wt%.
[0049] In the present invention, the ratio of the mass of the binder to the total mass of the metal salt, the aluminum compound and the silicon dioxide is preferably 0.02-0.05:10-30, more preferably 0.03-0.04:15-25, and further preferably 0.03-0.04:20.
[0050] In the present invention, the solvent preferably includes alcohol and water; the alcohol is preferably ethanol; the water is preferably deionized water; the mass ratio of water to ethanol is preferably 0.1 to 5:1, more preferably 0.5 to 3:1, and further preferably 1 to 2:1.
[0051] In the present invention, the ratio of the mass of the solvent to the total mass of the metal salt, the aluminum compound and the silicon dioxide is preferably 20.95 to 62.94:30, more preferably 25 to 55:30, and even more preferably 35 to 45:30.
[0052] In the present invention, the mixing is preferably ball milling; the equipment for ball milling is preferably a ball milling jar; the rotation speed of the ball milling is preferably 20 to 60 rpm, more preferably 30 to 50 rpm, further preferably 40 rpm, and the time is preferably 60 to 240 min, more preferably 120 to 180 min, further preferably 150 min.
[0053] After obtaining the slurry, the present invention sequentially dries, disperses and granulates the slurry to obtain a powder. In the present invention, the drying is preferably oven drying; the oven drying is preferably vacuum oven drying or normal pressure oven drying; the temperature of the vacuum oven drying is preferably 40 to 80°C, more preferably 50 to 70°C, and further preferably 60°C, and the pressure is preferably -0.10 to -0.05MPa, more preferably -0.08 to -0.06MPa, and further preferably -0.07MPa; the temperature of the normal pressure oven drying is preferably 50 to 100°C, more preferably 60 to 90°C, and further preferably 70 to 80°C.
[0054] In the present invention, the dispersion is preferably grinding dispersion; the rotation speed of the grinding dispersion is preferably 10 to 30 rpm, more preferably 20 to 30 rpm, and the time is preferably 10 to 60 min, more preferably 30 to 45 min.
[0055] In the present invention, the granulation is preferably vibrating screen granulation or spray drying granulation; the target particle size of the granulation is preferably 30 to 150 μm, more preferably 50 to 120 μm, and further preferably 80 to 100 μm.
[0056] After obtaining the powder, the present invention sequentially presses and sinters the powder to obtain a skeleton. In the present invention, the pressing preferably includes sequentially performing dry pressing and cold isostatic pressing; the dry pressing equipment is preferably a manual dry pressing machine or a semi-automatic dry pressing machine; the opening size of the porous mold used for the dry pressing is preferably adjusted according to the required block size, which can be 14mm×16mm~20mm×22mm (width×length), and more preferably 15mm×17mm~18mm×20mm; the porous mold is preferably adjusted according to the required block size, and more preferably 6-9g of powder is added to each hole, and more preferably 7-8g.
[0057] In the present invention, the dry pressing pressure is preferably 4-10 MPa, more preferably 6-8 MPa, and the holding time is preferably 0.5-2 min, more preferably 1-1.5 min. The present invention presses the skeleton blank by dry pressing to obtain an initial block.
[0058] In the present invention, the dry pressing preferably further comprises vacuum plastic sealing the dry pressed product.
[0059] In the present invention, the cold isostatic pressing pressure is preferably 100-300 MPa, more preferably 150-280 MPa, and the holding time is preferably 0.5-2 min, more preferably 1-1.5 min. The present invention makes the green body more compact and strong through cold isostatic pressing, which is convenient for sintering.
[0060] In the present invention, the sintering reaction is preferably carried out in an air atmosphere; the equipment for the sintering reaction is preferably a high-temperature sintering furnace with exhaust holes. The present invention uses a high-temperature sintering furnace with exhaust holes to carry out sintering in an air atmosphere, which is convenient for timely debinding.
[0061] In the present invention, the sintering reaction preferably includes a first heating stage, a first heat preservation stage, a second heating stage, a second heat preservation stage and a cooling stage, which are carried out in sequence; the heating rate of the first heating stage is preferably 2-7°C / min, more preferably 3-6°C / min, and further preferably 4-5°C / min, and the heating time is preferably 60-180min, more preferably 100-150min, and further preferably 120min. In the present invention, sodium carbonate is decomposed into sodium oxide and silicon dioxide at high temperature through the sintering reaction, and aluminum silicate reacts to form sodium aluminum silicate.
[0062] In the present invention, the temperature of the first insulation stage is preferably 400-500°C, more preferably 420-480°C, and further preferably 440-460°C, and the insulation time is preferably 120-300min, more preferably 150-250min, and further preferably 200min. In the first insulation stage, the vent is opened to the maximum for debinding, and after debinding (the first insulation stage is over), the vent is adjusted to less than 10% of the maximum opening to save energy consumption and improve the insulation effect.
[0063] In the present invention, the heating rate of the second heating stage is preferably 2.5-5°C / min, more preferably 3-4°C / min, further preferably 3.5°C / min, and the heating time is preferably 120-240min, more preferably 150-200min, further preferably 180min.
[0064] In the present invention, the temperature of the second insulation stage is preferably 700-1000°C, more preferably 800-900°C, and further preferably 850°C, and the insulation time is preferably 120-480 min, more preferably 180-360 min, and further preferably 240-320 min. Compared with a pure silica body, the sintering reaction temperature of the present invention is reduced by 400-700°C, and a higher hardness than a pure silica skeleton is obtained.
[0065] In the present invention, the temperature reduction stage preferably includes furnace cooling and air cooling performed in sequence; the final temperature of the furnace cooling is preferably below 200°C, more preferably below 180°C; the final temperature of the air cooling is preferably room temperature.
[0066] In the present invention, when the metal carbonate is sodium carbonate and potassium carbonate, the sintering reaction can be represented by the following chemical reaction:
[0067] Na 2 CO 3 =Na 2 O+CO 2 ↑;
[0068] 3SiO 2 +Na 2 O+Al 2 SiO 5 =2AlNaO 6 Si 2 ;
[0069] K 2 CO 3 =K 2 O+CO 2 ↑;
[0070] 3SiO2 +K 2 O+Al 2 SiO 5 =2AlKO 6 Si 2 .
[0071] The present invention generates sodium aluminum silicate and potassium aluminum silicate through sintering reaction, and because silicon dioxide is relatively excessive, the obtained silicon dioxide skeleton contains certain sodium aluminum silicate and potassium aluminum silicate.
[0072] After obtaining the skeleton, the present invention sequentially modifies, resin-infiltrates and solidifies the skeleton to obtain a silica composite ceramic doped with aluminum silicate. In the present invention, the modification preferably includes: mixing the skeleton, silane coupling agent and modifying liquid, and then sequentially performing vacuum infiltration and impregnation. The present invention can improve the bonding strength between the silica skeleton and the resin through modification.
[0073] In the present invention, the modified liquid preferably includes ethanol and water; the water is preferably deionized water; the mass ratio of ethanol to water is preferably 1:1; the pH value of the modified liquid is preferably 4-5, more preferably 5; the pH value adjuster of the modified liquid is preferably an organic acid; the organic acid preferably includes one or more of citric acid and acetic acid.
[0074] In the present invention, the silane coupling agent is preferably KH-570 silane coupling agent, more preferably KH-570 silane coupling agent solution; the concentration of the KH-570 silane coupling agent solution is preferably 1-10wt%, more preferably 3-7wt%, and further preferably 5wt%.
[0075] In the present invention, the mass ratio of the skeleton to the silane coupling agent is preferably 140:1-8, more preferably 140:2-6, further preferably 140:3-5, and further preferably 140:3-4; the mass ratio of the skeleton to the modifying liquid is preferably 1:0.5-5, more preferably 1:0.5-4, further preferably 1:1-3, and further preferably 1:1-2.
[0076] In the present invention, the temperature of the vacuum penetration is preferably room temperature, the vacuum degree is preferably -0.08 to -0.10 MPa, more preferably -0.09 MPa, and the penetration time is preferably 1 to 6 hours, more preferably 3 to 5 hours.
[0077] In the present invention, the immersion temperature is preferably 50 to 90° C., more preferably 60 to 80° C., and the immersion time is preferably 2 to 12 hours, more preferably 5 to 8 hours.
[0078] In the present invention, after the impregnation, the impregnated product is preferably air-dried and then baked; the drying temperature is preferably 80-120°C, more preferably 90-110°C, and further preferably 100°C, and the insulation time is preferably 3-12h, more preferably 5-10h, and further preferably 7h.
[0079] In the present invention, the resin infiltration preferably comprises the following steps: mixing the modified skeleton with the resin liquid and sequentially performing vacuum semi-infiltration, vacuum full-infiltration and vacuum plastic sealing.
[0080] In the present invention, the resin liquid preferably includes an initiator and a monomer; the mass percentage of the initiator in the resin liquid is preferably 0.1-1 wt %, more preferably 0.3-0.7 wt %, and further preferably 0.5 wt %.
[0081] In the present invention, the initiator is preferably a thermal initiator; the thermal initiator preferably includes one or more of benzoyl peroxide (BPO), tert-butyl peracetate, dicumyl peroxide (DCP) and tert-butyl peroxy-2-ethylhexanoate (TBPO).
[0082] In the present invention, the monomers preferably include acrylate monomers and diluent monomers; the mass ratio of the acrylate monomers to the diluent monomers is preferably 3 to 8:2, more preferably 4 to 6:2, and further preferably 7:3.
[0083] In the present invention, the acrylic ester monomer preferably includes one or both of bisphenol A propylene glycol dimethacrylate (BIS-EMA) and urethane dimethacrylate (UDMA); the diluent monomer preferably includes one or both of triethylene glycol dimethacrylate (TEGDMA) and ethylene glycol dimethacrylate (EGDMA).
[0084] In the present invention, the method for preparing the resin solution is preferably: mixing an initiator and a monomer; the mixing speed is preferably 100 to 300 rpm, more preferably 200 rpm, and the mixing time is preferably 60 to 300 min, more preferably 120 to 240 min.
[0085] In the present invention, the pressure of the vacuum semi-permeation is preferably 0.1-1 Pa, more preferably 0.3-0.6 Pa, and the permeation time is preferably 6-72 h, more preferably 24-48 h; the equipment for the vacuum semi-permeation is preferably a vacuum permeameter.
[0086] In the present invention, the vacuum semi-permeation is preferably performed by placing the frame into the resin liquid, and the resin liquid is immersed to 1 / 3 to 1 / 2 of the height of the frame for semi-permeation.
[0087] In the present invention, the pressure of the vacuum full penetration is preferably 0.1-1 Pa, more preferably 0.3-0.6 Pa, and the penetration time is preferably 24-240 h, more preferably 48-72 h; the equipment for the vacuum full penetration is preferably a vacuum permeameter.
[0088] In the present invention, the vacuum full penetration is preferably: the vacuum semi-penetrated skeleton is further injected with resin liquid until the vacuum semi-penetrated skeleton is immersed, and then full penetration is performed. The present invention vacuum-seales the infiltrated aluminum silicate-doped silica skeleton to prevent oxygen inhibition.
[0089] In the present invention, the curing preferably includes a first curing and a second curing performed sequentially; the temperature of the first curing is preferably 60-100°C, more preferably 70-90°C, further preferably 80-90°C, the pressure is preferably 120-180MPa, more preferably 140-160MPa, and the holding time is preferably 1-6h, more preferably 3-4h; the temperature of the second curing is preferably 100-130°C, more preferably 110-120°C, the pressure is preferably 200-350MPa, more preferably 250-300MPa, and the holding time is preferably 2-12h, more preferably 5-8h.
[0090] In the present invention, after curing, the obtained cured product is preferably subjected to surface treatment; the surface treatment is preferably: chamfering, polishing, sticking a handle, printing, testing and packaging the cured product in sequence.
[0091] The present invention also provides the use of the aluminum silicate-doped silica composite ceramic described in the above scheme or the aluminum silicate-doped silica composite ceramic obtained by the preparation method described in the above scheme in the field of dentistry.
[0092] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0093] Example
[0094] The method for preparing the silicon dioxide composite ceramic doped with aluminum silicate in this embodiment comprises the following steps:
[0095] According to Tables 1 to 3, carbonate, aluminum silicate and silicon dioxide were weighed according to the proportions, the ratio of the mass of the binder to the total mass of the carbonate, aluminum compound and silicon dioxide was 0.2:20; the ratio of the total mass of ethanol and water to the total mass of the carbonate, aluminum compound and silicon dioxide was 1:1, and the mass ratio of water to ethanol was 1:1. The carbonate, aluminum compound, silicon dioxide, 2 wt% polyvinyl alcohol aqueous solution, ethanol and water were ball-milled at 60 rpm for 240 min to obtain a slurry;
[0096] The slurry was sequentially subjected to vacuum drying at 80°C (-0.10MPa), grinding and dispersion at 30rpm for 60min, and granulation by spray drying to obtain a powder with a particle size range of 30 to 150μm;
[0097] The powder is sequentially subjected to dry pressing, vacuum plastic sealing, cold isostatic pressing and sintering reaction, wherein the sintering reaction is sequentially carried out in the first heating stage, the first heat preservation stage for debinding, the second heating stage, the second heat preservation stage and the cooling stage, wherein the cooling stage is carried out in the furnace to cool to 200°C, and then the furnace door is opened to air cool to room temperature;
[0098] After the sintering reaction, the obtained skeleton is modified: the skeleton, a 2wt% KH-570 silane coupling agent solution and a modifying liquid are mixed, and then vacuum infiltrated at room temperature -0.08MPa for 6h, then immersed at 80°C for 5h, and then the impregnated product is dried and dried at 100°C for 12h; the modifying liquid is ethanol and deionized water in a mass ratio of 1:1, and the pH value is 4; the mass ratio of the skeleton to the silane coupling agent is 140:2, and the mass ratio of the skeleton to the modifying liquid is 1:2, to obtain a modified skeleton, and the porosity and bulk density of the modified skeleton are measured by a water boiling method.
[0099] The initiator and the monomer are mixed at 300 rpm for 120 min, wherein the initiator is benzoyl peroxide, the monomer is an acrylate monomer and a diluent monomer in a mass ratio of 5:2, the acrylate monomer is bisphenol A propylene glycol dimethacrylate, and the diluent monomer is triethylene glycol dimethacrylate, to obtain a resin liquid, wherein the mass percentage of the initiator in the resin liquid is 0.1 wt%;
[0100] The modified skeleton is placed in resin liquid, and the resin liquid is immersed to 1 / 3 of the height of the modified skeleton. It is semi-permeated at 1Pa vacuum for 36 hours, and the resin liquid is continuously injected until the modified skeleton is immersed. It is fully permeated at 1Pa vacuum for 48 hours, and vacuum-sealed. It is pressurized at 80°C and 150MPa for 1 hour in an autoclave, and then heated to 120°C and 300MPa for pressurized curing for 2 hours. After cooling, the ceramic block is taken out, chamfered, polished, glued to a handle, printed, tested and packaged to obtain a silica composite ceramic doped with aluminum silicate.
[0101] For comparison, the total mass of powder used for each green body in Tables 1 to 3 is 8.0 g. A porous mold and a semi-automatic dry press are used. The dry pressing pressure is 6 MPa and the holding time is 60 s. The cold isostatic pressing pressure is 280 MPa and the holding time is 60 s. The other parameters recorded in Tables 1 to 3 are carried out in accordance with Tables 1 to 3.
[0102] Table 1 Sintering curves of examples and comparative examples
[0103]
[0104]
[0105] Table 2 Raw material ratio, physical parameters of skeleton
[0106]
[0107] Table 3 Performance parameters of silica composite ceramics doped with aluminum silicate
[0108]
[0109]
[0110] According to Tables 1 to 3, it can be seen that "Comparative Example 1" is a skeleton sintered from pure micron-sized silica powder. The sintering reaction temperature is high, and the obtained skeleton has a pore size of 520.3 nm and a porosity of 40.5%, which is convenient for resin infiltration. A well-infiltrated skeleton can be obtained within 36 hours, but the obtained composite ceramic has poor flexural strength, especially the hardness is only 1.8 GPa;
[0111] Comparative Example 2 was sintered with Evonik nano-sodium aluminum silicate powder, with a pore size of 30 nm and a porosity of 35.6%. Due to the small pore size, it took 240 hours of continuous vacuum resin infiltration to basically complete the infiltration, and the resulting composite ceramic had low flexural strength and the highest hardness.
[0112] Example 1 has the lowest flexural strength and high hardness, which may be due to the formation of closed pores during the sintering reaction, which is not completely in accordance with the chemical molar ratio reaction, but provides a direction for improving the hardness of the composite ceramic;
[0113] The skeleton pore size of the silica composite ceramic doped with aluminum silicate in Example 5 is 341.2 nm, and the porosity is 37.5%. The skeleton pore size is moderate, which is convenient for resin penetration. The data show that it is completely penetrated in 72 hours, has the best comprehensive mechanical properties, takes into account both bending strength and hardness, and is the optimal choice.
[0114] Table 4 Pore diameter of the skeletons prepared in Example 5 and Comparative Example 2
[0115]
[0116] It can be seen from Table 4 that the pore size of the silica skeleton of the embodiment is increased from 30 nm of the nano-scale sodium aluminum silicate powder to 341 nm, and the average pore size of the skeleton is increased by 10 times, which is more conducive to resin penetration.
[0117] It can be seen from the above embodiments that the skeleton pore size of the aluminum silicate-doped silica composite ceramic provided by the present invention is relatively large, the pore size is between 100 and 600 nm, the porosity is high, and the resin liquid is easy to fully penetrate the skeleton to form an interlocking structure of the resin and the skeleton, and the transparency is better, the mechanical properties such as flexural strength and elastic modulus are more excellent, and the ability to resist crack propagation is stronger.
[0118] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A silicon dioxide composite ceramic doped with aluminum silicate, characterized in that: It includes a frame and a resin that forms an interlaced interlocking structure with the frame; The mass content of the skeleton is 70-90%, and the mass content of the resin is 10-30%; The general formula of the skeleton is mX a O b ·pAl2O3·qSiO2, where m, p and q are the molar numbers of the oxide, 0.01≤m≤1, 0.05≤p≤1, q≥2, a ranges from 1 to 2, and b ranges from 1 to 3; The X in the skeleton a O b It is a mixture of sodium oxide and other metal oxides or sodium oxide; the other metal oxides include one or more of potassium oxide, lithium oxide, alkaline earth metal oxide and transition metal oxide; the total molar number of the other metal oxides is less than the molar number of sodium oxide; The pore size of the skeleton is 100-600 nm, and the porosity is 20-40%.
2. The method for preparing the aluminum silicate-doped silicon dioxide composite ceramic according to claim 1, characterized in that: The following steps are involved: (1) mixing an aluminum compound, silicon dioxide, a metal salt, a binder and a solvent to obtain a slurry; the metal salt is a carbonate; the carbonate includes one or more of sodium carbonate, potassium carbonate, lithium carbonate, alkaline earth metal carbonate and transition metal carbonate; (2) drying, dispersing and granulating the slurry in sequence to obtain a powder; (3) pressing and sintering the powder in sequence to obtain a skeleton; (4) modifying, resin-infiltrating and curing the skeleton in sequence to obtain a silicon dioxide composite ceramic doped with aluminum silicate; the modification comprises: mixing the skeleton, silane coupling agent and modifying liquid, and then vacuum-infiltrating and impregnating them in sequence; The modifying liquid comprises ethanol and water.
3. The preparation method according to claim 2, characterized in that: The sintering reaction is carried out in an air atmosphere; the sintering reaction includes a first heating stage, a first heat preservation stage, a second heating stage, a second heat preservation stage and a cooling stage which are carried out in sequence.
4. The preparation method according to claim 3, characterized in that: The heating rate of the first heating stage is 2-7°C / min, and the heating time is 60-180min; The temperature of the first insulation stage is 400-500°C, and the insulation time is 120-300 minutes; The heating rate of the second heating stage is 2.5-5°C / min, and the heating time is 120-240min; The temperature of the second insulation stage is 700-1000°C, and the insulation time is 120-480 minutes; The temperature reduction stage includes furnace cooling and air cooling performed in sequence; The final temperature of the furnace cooling is below 200° C.; the final temperature of the air cooling is room temperature.
5. The preparation method according to any one of claims 2 to 4, characterized in that: The mixing is ball milling mixing; the rotation speed of the ball milling mixing is 20 to 60 rpm, and the time is 60 to 240 minutes.
6. The preparation method according to claim 2 or 3, characterized in that: The drying is oven drying; the oven drying is vacuum oven drying or normal pressure oven drying; The temperature of the vacuum drying is 40 to 80° C. and the pressure is -0.10 to -0.05 MPa; The temperature of the normal pressure drying is 50-100°C.
7. The preparation method according to claim 2 or 4, characterized in that: The dispersion is grinding dispersion; the rotation speed of the grinding dispersion is 10 to 30 rpm and the time is 10 to 60 minutes.
8. The preparation method according to claim 2 or 3, characterized in that: The granulation is vibrating screen granulation or spray drying granulation; the target particle size of the granulation is 30 to 150 μm.
9. The preparation method according to claim 2 or 4, characterized in that: The pressing comprises dry pressing and cold isostatic pressing in sequence; the pressure of the dry pressing is 4-10 MPa, and the holding time is 0.5-2 min.
10. The preparation method according to claim 9, characterized in that: The cold isostatic pressing pressure is 100-300 MPa, and the holding time is 0.5-2 min.
11. The preparation method according to claim 2, characterized in that: The resin infiltration comprises the following steps: mixing the modified skeleton with the resin liquid and sequentially performing vacuum semi-infiltration, vacuum full-infiltration and vacuum plastic sealing; the pressure of the vacuum full-infiltration is 0.1-1 Pa, and the infiltration time is 24-240 hours.
12. Use of the aluminum silicate-doped silica composite ceramic according to claim 1 or the aluminum silicate-doped silica composite ceramic obtained by the preparation method according to any one of claims 2 to 11 in the field of dentistry.
Citation Information
Patent Citations
High-hardness wear-resistant resin-permeable ceramic composite material as well as preparation method and application thereof
CN115894001A